CD40‐Independent Help by Memory CD4 T Cells Induces Pathogenic Alloantibody But Does Not Lead to Long‐Lasting Humoral Immunity. Issue 11 (18th September 2013) - Rabant, M.; Gorbacheva, V.; Fan, R.; Yu, H.; Valujskikh, A.
Abstract: CD40/CD154 interactions are essential for productive antibody responses to T‐dependent antigens. Memory CD4 T cells express accelerated helper functions and are less dependent on costimulation when compared with naïve T cells. Here, we report that donor‐reactive memory CD4 T cells can deliver help to CD40‐deficient B cells and induce high titers of IgG alloantibodies that contribute to heart allograft rejection in CD40−/− heart recipients. While cognate interactions between memory helper T and B cells are crucial for CD40‐independent help, this process is not accompanied by germinal center formation and occurs despite inducible costimulatory blockade. Consistent with the extrafollicular nature of T/B cell interactions, CD40‐independent help fails to maintain stable levels of serum alloantibody and induce differentiation of long‐lived plasma cells and memory B cells. In summary, our data suggest that while CD40‐independent help by memory CD4 T cells is sufficient to induce high levels of pathogenic alloantibody, it does not sustain long‐lasting anti‐donor humoral immunity and B cell memory responses. This information may guide the future use of CD40/CD154 targeting therapies in transplant recipients containing donor‐reactive memory T cells. Abstract : These results in a murine model of heart transplantation show that donor‐reactive memory CD4 T cells induce pathogenic IgG alloantibody in the absence of CD40/CD154 interactions but fail to promote differentiation of longlived plasma cells and memory B cells under these conditions.